Answer:
A
Step-by-step explanation:
it's A lol
.................................
Answer:
3x² + 6x - 24 = 0
(3x - 6)(x + 4) = 0
x = -4 , x = 2 when y = 0
Step-by-step explanation:
3x² + 6x - 24 = 0
(3x - 6)(x + 4) = 0
Means
3x - 6 = 0 ⇒ 3x = 6 ⇒ x = 6 ÷ 3 = 2
x + 4 = 0 ⇒ x = -4
The Parabola which represents the quadratic equation intersects x-axis at
points (2 , 0) and (-4 , 0)
Answer: I think b
Step-by-step explanation:
Answer:
2(39)(31)+2(39^2)=5460m^2
Step-by-step explanation:
Your Answer: G(x) = (x − 5)²
I just finished my semester exam, and this was one of the questions. I guessed on this question because I had no clue of what the answer was, and lucky me, I got the question right :D
Hope this helps y'all with your test :)